Predictors Of Antihypertensive Drug (AHD) Therapy Failure Among Elderly Patients At Sangkrah Public Health Center, Surakarta. - Aditya Raka Fahri; Siwi Hastuti; Bangkit Riska Permata (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension is the most common non-communicable disease in Indonesia with a prevalence of 34.1% in adults aged 18 years and above, with the elderly at high risk due to physiological changes such as decreased kidney function and arterial stiffness. This study aims to identify predictors of antihypertensive drug (ADH) therapy failure and dominant factors in elderly patients at the Sangkrah Surakarta Community Health Center. A quantitative analytical observational study with a cross-sectional design involved 96 elderly respondents (≥60 years) with ADH therapy for at least 3 months, selected the Lemeshow formula and total sampling. Medical record data and questionnaires covering demographics, knowledge, adherence (MMAS-8), lifestyle, were analyzed univariately, bivariately (Chi-Square), multivariate (logistic regression) using SPSS. The results showed 72.9% were male, 71.9% had good knowledge, 80.2% were compliant; Age (p=0.629), gender (p=0.622), and education (p=0.559) were not significant, but knowledge significantly influenced adherence (p=0.011). Low knowledge was the main predictor of therapy failure (BP ≥140/90 mmHg). Intensive education is recommended to improve adherence.